2022
DOI: 10.1007/s00127-022-02405-9
|View full text |Cite
|
Sign up to set email alerts
|

‘C’mon, let’s talk: a pilot study of mental health literacy program for Filipino migrant domestic workers in the United Kingdom

Abstract: Purpose This pilot study of a culturally adapted online mental health literacy (MHL) program called ‘Tara, Usap Tayo!’ (C’mon, Let’s Talk) aims to assess the acceptability, appropriateness, feasibility, and potential effectiveness in improving the help-seeking behavior of Filipino migrant domestic workers in the United Kingdom (UK). Methods Using mixed methods, we conducted a non-randomized single-group study of the online MHL program with 21 participants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Research by Hall et al (2018) found that most Filipino domestic workers in Macao owned a smartphone and had access to the Internet, given the flexibility and effectiveness of online platforms for disseminating health knowledge. Nonetheless, existing research on health literacy for Filipino domestic workers currently focuses on mental health literacy in the United Kingdom, in which a lack of effectiveness among asynchronous, synchronous, internet-based education of health literacy promotion program was examined ( Martinez et al, 2022 ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Research by Hall et al (2018) found that most Filipino domestic workers in Macao owned a smartphone and had access to the Internet, given the flexibility and effectiveness of online platforms for disseminating health knowledge. Nonetheless, existing research on health literacy for Filipino domestic workers currently focuses on mental health literacy in the United Kingdom, in which a lack of effectiveness among asynchronous, synchronous, internet-based education of health literacy promotion program was examined ( Martinez et al, 2022 ).…”
Section: Review Of Literaturementioning
confidence: 99%